Adaptive NN finite-time inverse optimized formation fault-tolerant control for multi-USV systems with actuator faults - Jiaming Zhang; Yi Zuo; Shaocheng Tong (Ocean Engineering, 2026)

Role of adiabatic heating in winter warming over the Tibetan Plateau - Jiaming Tan; Meiyu Chang; Zouxing Lin; Zhiyan Zuo (Science China Earth Sciences, 2025)

Calibration of the Solar X-ray Detector on-board the Macao Science Satellite-1B for Soft X-ray Detection - Man-Hei Ng; Xiaoping Zhang; Jianwu Chen; Yongqiang Shi; Fuchang Zuo; Wenxi Peng; Weichun Fu; Liansheng Li; Pengwei Luo; Chi-Long Tang; Guozheng Zhang; Zhiwu Mei; et al. (Science China Earth Sciences, 2025)

Insights into the effects of environmental factors on phytoplankton and microzooplankton at a basin scale: diversity, assembly mechanisms, and co-occurrence networks - Yanjun Shen; Xinxin Zhou; Jiaming Zhang; Qinghua Li; Yufeng Zhang; Qing Zuo (Frontiers in Marine Science, 2024)
Mastering the characteristics of planktonic microbial communities under the influence of basin-scale environmental factors can provide scientific basis to develop more targeted protection and restoration measures. Here, an environmental DNA metabarcoding technology was applied to investigate the phytoplankton and microzooplankton simultaneously along the whole basin of Jialing River, one of the most important rivers in Southwest China with large scale altitude gradient and water temperature discrepancy. Along the river-way from upper to lower reach, an upward trend in richness of both phytoplankton and microzooplankton was observed with significant positive and negative correlations to water temperature and altitude (Spearman correlation, p < 0.05), respectively. Significant variations in their compositions along the river were also uncovered with Chrysophyta and Foraminifera was potential keystones recognized by the co-occurrence network analysis. Additionally, exponential distance-decay of similarities were detected for both phytoplankton and microzooplankton, which were stronger for phytoplankton. Based on the results of variation partitioning analysis and null model, variations in phytoplankton communities were more governed by environmental selection than those in microzooplankton. Furthermore, the co-occurrence network showed a declining trend in the complexity and stability from the upper to lower reaches. These findings could serve to establish a basis for the investigation of phytoplankton and microzooplankton communities in rivers with multiple artificial modifications.

Live chicken body fat measurement technology based on bio-electrical impedance - Jiaming Zuo; Jinping Liang; Shangshang Cheng; Yuelin Deng; Zhenhui Li; Qinghua Nie; Dexiang Zhang; Xiquan Zhang; Zhen Li; Hongmei Li (Computers and Electronics in Agriculture, 2024)

Sphere2Vec: A general-purpose location representation learning over a spherical surface for large-scale geospatial predictions - Gengchen Mai; Yao Xuan; Wenyun Zuo; Yutong He; Jiaming Song; Stefano Ermon; Krzysztof Janowicz; Ni Lao (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Discovery of the Early Paleozoic Akechukesai high-Mg diorites in the western segment of East Kunlun Orogenic Belt and its constraints on the mechanism of break-off from Proto-Tethys oceanic subducted slab - Chao Wang; Fengyue Sun; Dongwei Liu; Lei Zuo; Tuofei Zhao; Jiaming Yan (Geosciences Journal, 2022)

Blood Loss Leads to Increase in Relative Abundance of Opportunistic Pathogens in the Gut Microbiome of Rabbits - Junjie Yang; Jiaming Zhang; Changying Zhao; Zhongtao Gai; Xiaofeng Mu; Ye Wang; Chunling Zhang; Zhenzhen Su; Lihe Gao; Dequan Zhu; Zhiwen Zuo; Xueyuan Heng; et al. (Current Microbiology, 2020)